Microstructural characteristics in Babbitt coatings deposited by LPCS - Tillmann, Wolfgang; Hagen, Leif; Abdulgader, Mohamed; Kensy, Mark Dennis; Paulus, Michael (Technische Universität Dortmund, 2020)
Studies have already established that the mechanical properties of Babbitt coatings significantly depend on the microstructural characteristics, such as the amount and distribution of intermetallic compounds dispersed in a soft solid solution matrix. For Sn–Sb–Cu-based Babbitt coatings, the formation of SbSn- and CuSn-based precipitates has a substantial influence on the resulting microhardness and thus determines the maximum load carrying capacity. Thermal spraying of Sn-based Babbitt coatings results in a relatively more refined structure of these precipitates than in common manufacturing processes, such as casting, due to the thermal processing conditions. This study aims to evaluate the effect of the temperature of the propellant gas and substrate temperature on the microstructural characteristics of Sn–Sb–Cu-based Babbitt coatings deposited by low pressure cold spraying (LPCS). The deposits were examined for their phase composition, microhardness and mesoscopic structure. It was found that the coatings were mainly composed of Sb2Sn23, Sb0.49Sn0.51 and Sorosite (CuSn or CuSb0.115Sn0.835), regardless of the substrate temperature or temperature of the propellant gas to be investigated. For a gas temperature above 300 °C, an increased microhardness was observed, which correlates with the appearance of a more homogenous distribution of Sb0.49Sn0.51 dispersed in a soft Sn-rich solid solution matrix.
Coatings;10(7)
Keywords: Babbitt; Thermal spraying; Low pressure cold spraying; 620; 670; Nichteisenmetall; Thermisches Spritzen; Kaltspritzen